ANALISIS KEMAMPUAN BERPIKIR KRITIS BIOLOGI SISWA SAAT PEMBELAJARAN DARING - Ismi Rindu Adinda; Uswatun Hasanah; Sri Banun (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2021)
This study aims to analyze the critical thinking skills of MAN students during online learning. This research includes descriptive research with a quantitative approach. The research subjects were 54 students of class XI MIA 3 and XI MIA 4 MAN Tanjungbalai by using simple random sampling technique. The data were collected by using a question instrument in the form of essay as many as ten questions. The data analysis technique used in this research is descriptive statistical processing. The results showed that the indicator giving a simple explanation had an average value of 66.66 with a sufficient category, the indicator determining the basis for decision making had an average value of 56.94 with a less category, the indicator drew conclusions with an average value of 52.77 with a poor category, the indicator provides further explanation with an average value of 59.72 with less category, tactics and strategy indicator has an average value of 58.79 with less category, critical thinking ability of students of class XI MIA 3 and XI MIA 4 MAN Tanjungbalai as a whole when online learning has an average value of 59.57 in the less category. One of the efforts that can improve students' critical thinking skills is using the right learning method such as problem-based learning.